(untitled) (Research, Society and Development, 2021)
Objective: To analyze the oxyhemodynamic impact of a bed bath without water temperature control performed within 20 minutes in patients with acute myocardial infarction. Method: Uncontrolled clinical trial conducted from June 2015 to March 2016, with 23 infarcted patients in the coronary care unit of a private hospital in Niterói. Blood flow, cardiac contractility and oximetry variables were recorded by a cardiographic bioimpedance device before, during and after the bed bath. Analysis of variance, multiple linear regression, Friedman test and t-student test were performed, with a significance level of 5% and a 95% confidence interval. Results: There was minor variation in heart rate and blood pressure in the three moments. Cardiac index and stroke volume showed significant variations, without causing clinical instability. Conclusion: the bed bath without water temperature control did not significantly affect blood flow variables.